ANTI-INFLAMMATORY AND ANTI-GRANULOMA ACTIVITY OF SULFORAPHANE, A NATURALLY OCCURRING ISOTHIOCYANATE FROM BROCCOLI (BRASSICA OLERACEA) - Mohanty, Sangeeta; Pal, Abhisek; Konkimalla, V Badireenath; Chandra Si, Sudam (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study was to establish the anti-inflammatory activity of sulforaphane (SFN) in different acute and subchronic models of inflammation. Methods: The anti-inflammatory activity of SFN was evaluated by the secretion of proinflammatory cytokines in rat peripheral blood mononuclear cells (interleukin-6 [IL-6] and tumor necrosis factor alpha [TNF-α]) which are important mediators of inflammation as determined by enzyme-linked immunosorbent assay. Furthermore, paw volume was determined in various acute models of inflammation, and percentage inhibition of granuloma tissue was assessed by cotton pellet-induced granuloma model. From serum, serum glutamic pyruvic transaminase, serum glutamic oxaloacetic transaminase, and alkaline phosphatase levels were determined which is followed by assay for estimation of antioxidants such as superoxide dismutase (SOD), catalase, and glutathione (GSH). Results: SFN showed significant anti-inflammatory activity against paw edema induced by carrageenin/histamine/egg-albumin. A remarkable control in inflammation was observed most notably at the highest test dose of 5 mg/kg in the subchronic granuloma model. In addition, the release of inflammatory cytokines such as IL-6 and TNF-α which is responsible for inflammatory activity gets attenuated by SFN (∗p<0.05; ∗∗p< 0.01). Moreover, toxic control rats showed significant decreased levels of GSH, catalase, and SOD and increased the level of serum hepatic enzymes which gets reversed by SFN in dose-dependent manner. Conclusions: The present findings demonstrated that SFN can recover inflammation by inhibiting TNF-α and IL-6 in inflammation process.